Artificial Intelligence Utilization as a Correlate of Management Effectiveness in Public Tertiary Institutions in Edo State, Nigeria - Enowoghomwenma, D. E.; Marchie, N. C. (NIU Journal of Educational Research; Vol 12 No 2 (2026): NIU Journal of Educational Research, Vol. 12, No. 2, June 2026, 2026)
The increasing adoption of Artificial Intelligence (AI) in higher education presents significant opportunities for improving institutional management; however, empirical evidence on its utilization and relationship with management effectiveness in Nigerian tertiary institutions remains limited. This study examined the relationship between Artificial Intelligence utilization and management effectiveness in public tertiary institutions in Edo State, Nigeria. Anchored on the Technology Acceptance Model and Systems Theory, the study adopted a correlational research design. The population comprised academic staff, non-teaching staff, and students from Federal and State-owned tertiary institutions in Edo State, from which a sample of 300 respondents was selected using a multi-stage sampling procedure. Data were collected using the validated and pilot-tested Artificial Intelligence Utilization and Management Effectiveness Questionnaire (AIUMEQ) and analysed using mean, standard deviation, and Pearson Product Moment Correlation at the 0.05 level of significance. The findings revealed that the level of Artificial Intelligence utilization in the institutions was low, while management effectiveness was moderate. The study further established a statistically significant positive relationship between Artificial Intelligence utilization and management effectiveness, indicating that institutions with higher levels of AI Utilization tended to demonstrate better planning, communication, coordination, monitoring, and decision-making processes. The study concluded that Artificial Intelligence utilization is positively associated with management effectiveness and represents a strategic resource for enhancing institutional administration. It recommended increased investment in AI infrastructure, capacity building, and policy frameworks to promote the effective integration and utilization of AI technologies into tertiary institution management and improve organisational effectiveness. Keywords: Artificial Intelligence, Management Effectiveness, Public Tertiary Institutions, Educational Management, Technology Utilization.